2018
DOI: 10.1080/10408398.2018.1425977
|View full text |Cite
|
Sign up to set email alerts
|

The effects of probiotics in lactose intolerance: A systematic review

Abstract: Over 60 percent of the human population has a reduced ability to digest lactose due to low levels of lactase enzyme activity. Probiotics are live bacteria or yeast that supplements the gastrointestinal flora. Studies have shown that probiotics exhibit various health beneficial properties such as improvement of intestinal health, enhancement of the immune responses, and reduction of serum cholesterol. Accumulating evidence has shown that probiotic bacteria in fermented and unfermented milk products can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(130 citation statements)
references
References 34 publications
0
110
0
4
Order By: Relevance
“…Some evidence exists for certain probiotics to help manage blood lipids in people with mild hypercholesterolemia (Wang et al 2018). Probiotics can improve lactose digestion in lactose intolerant people, with most evidence showing that lactose consumed in yogurt with live cultures is better tolerated than the same amount of lactose consumed without live cultures (Oak & Jha 2018). A recent systematic review evaluated the role of probiotics in the management of lower gastrointestinal symptoms (Hungin et al 2018).…”
Section: Do Probiotics Have Any Benefit For Generally Healthy People?mentioning
confidence: 99%
“…Some evidence exists for certain probiotics to help manage blood lipids in people with mild hypercholesterolemia (Wang et al 2018). Probiotics can improve lactose digestion in lactose intolerant people, with most evidence showing that lactose consumed in yogurt with live cultures is better tolerated than the same amount of lactose consumed without live cultures (Oak & Jha 2018). A recent systematic review evaluated the role of probiotics in the management of lower gastrointestinal symptoms (Hungin et al 2018).…”
Section: Do Probiotics Have Any Benefit For Generally Healthy People?mentioning
confidence: 99%
“…The use of probiotics and prebiotics could be used as therapeutic approaches against diseases. In fact, it was recently reported that consumption of probiotics had an overall positive relationship with lactose intolerance [46]. In order to determine the mechanism by which fermented milk consumption confers health benefits, serum metabolome was measured in 14 healthy males in a randomized crossover study following consumption of either non-fermented milk or yoghurt.…”
Section: Health Benefits Of Fermented Milk Productsmentioning
confidence: 99%
“…Igarashi et al . ) and lactose maldigestion (Oak & Jha ). Interestingly, there is more convincing evidence for live yogurt cultures having an ameliorating effect on lactose maldigestion and this has led to an EFSA health claim (EFSA ).…”
Section: Setting the Scene – A Summary Of The Presentation On The Evimentioning
confidence: 99%